La negación del tiempo como postulado fantástico en "Tlön Uqbar, Orbis Tertius" de Jorge Luis Borges - Anchante Arias, Jim Alexander (2022)
This article is an analysis of the tale «Tlön Uqbar, Orbis Tertius» by Jorge Luis Borges, which is included in his book Ficciones (1944). The conception of time in this story is analyzed from the fantastic postulate of the denial of time. To this end, a thematic link is established with the text «Nueva refutación del tiempo». Based on theories of the fantastic, it is argued that Tlön’s imaginary world is an inverse representation of our «reality». With this, the configuration of a bookish reality is established that, although it is textual in nature, can affect and alter what we know as the world.